EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE THE POWER OF TWO AND FOUR TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VIII SMPN 51 MERANGIN - Muhammad Jainuri (Matedukasia, 2016)
The purpose of this study was to describe mathematical communication skills using the cooperative learning model of the power of two and four types better than conventional learning. The study used a quantitative approach with the experimental method. The study population was all eighth grade students of SMPN 51 Merangin which numbered two classes with samples class VIII A as the experimental class and class VIII B as the control class. The instruments used are test questions mathematical communication skills in the form of descriptions. The results of data analysis requirements indicate that the data of the two sample classes are not normally distributed and have a homogeneous variance. Hypothesis testing uses two-independent formula samples with U-test (Mann Whitney). Based on the results of the analysis of research data shows that Sig. greater than α or 0.038 <0.05 in the one-party test. Because Sig. <α then Ho is rejected and H1 is accepted, so that it can be concluded that mathematical communication skills using the synectic learning model are better than conventional learning of class VIII students of SMP 51 Merangin.